2018
DOI: 10.1111/jse.12305
|View full text |Cite
|
Sign up to set email alerts
|

Pteridryaceae: A new fern family of Polypodiineae (Polypodiales) including taxonomic treatments

Abstract: We undertook phylogenetic analyses to resolve the relationships of Pteridrys and related taxa based on six plastid markers (atpA, atpB, matK & rps16‐matK, rbcL, rps4 & rps4‐trnS, and trnL & trnL‐F) and nuclear pgiC. We included 195 accessions representing approximately 147 species in 38 genera, and seven of the nine families in Polypodiineae (eupolypods I). Tectariaceae s.l. (i.e., Arthropteris, Draconopteris, Hypoderris, Malaifilix, Pteridrys, Tectaria, and Triplophyllum in addition to Polydictyum) is recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 97 publications
(239 reference statements)
0
13
2
1
Order By: Relevance
“…Others (SCO75 AA MSC, SCO60 AA MSC, MCO NT MSC, MCO AA MSC, codon positions one and two) recovered a clade consisting of Pteridrys and Tectaria sister to a clade of Arthropteris , Oleandraceae, Davalliaceae, and Polypodiaceae. Despite the different topologies recovered in our analyses, several recent studies have recovered Tectariaceae to be monophyletic (including all three genera sampled here) ( Liu et al, 2014 ; Zhang et al, 2016 ; Zhou et al, 2018 ) although Zhou et al (2018) suggest a new family (Pteridryaceae) be recognized. While Du et al (2021) separate Tectariaceae from Pteridryaceae ( Zhou et al, 2018 ) and Arthopteridaceae (suggested by Liu et al, 2013 , but not recognized by The Pteridophyte Phylogeny Group, 2016 ), they found the three families form a clade sister to the remaining eupolypods I.…”
Section: Discussioncontrasting
confidence: 61%
“…Others (SCO75 AA MSC, SCO60 AA MSC, MCO NT MSC, MCO AA MSC, codon positions one and two) recovered a clade consisting of Pteridrys and Tectaria sister to a clade of Arthropteris , Oleandraceae, Davalliaceae, and Polypodiaceae. Despite the different topologies recovered in our analyses, several recent studies have recovered Tectariaceae to be monophyletic (including all three genera sampled here) ( Liu et al, 2014 ; Zhang et al, 2016 ; Zhou et al, 2018 ) although Zhou et al (2018) suggest a new family (Pteridryaceae) be recognized. While Du et al (2021) separate Tectariaceae from Pteridryaceae ( Zhou et al, 2018 ) and Arthopteridaceae (suggested by Liu et al, 2013 , but not recognized by The Pteridophyte Phylogeny Group, 2016 ), they found the three families form a clade sister to the remaining eupolypods I.…”
Section: Discussioncontrasting
confidence: 61%
“…Plastomes of 208 taxa of Polypodiales, representing 109 genera and all 26 families recognized by PPG I (2016), plus Arthropteridaceae (Liu et al, 2013) and Pteridryaceae (Zhou et al, 2018), were gathered including 163 plastomes of 99 genera generated in this study plus 45 plastomes accessed via GenBank (Tables 1 and S1). Plastomes of six taxa including two newly generated plastomes from orders Cyatheales and Salviniales were employed as outgroups (Tables 1 and S1).…”
Section: Sampling Sequencing and Genome Assemblymentioning
confidence: 99%
“…Plastome sequences of 124 taxa, representing all 50 recognized families and 11 orders of ferns (following Liu et al, 2013 ; PPG I, 2016 ; Zhou et al, 2018 ), were gathered in this study, which includes 42 novel plastomes from 15 families with a focus on Hymenophyllales and Gleicheniales ( Table 1 ; Supplementary Table 1 ), plus 82 plastomes accessed via GenBank ( Table 1 ). Plastomes of two seed plants and one lycophyte were employed as outgroups ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%